Nerve ultrasound can identify treatment‐responsive chronic neuropathies without electrodiagnostic features of demyelination. Issue 4 (24th July 2019) - Goedee, H. Stephan; Herraets, Ingrid J. T.; Visser, Leo H.; Franssen, Hessel; van Asseldonk, Jan‐Thies H.; van der Pol, W. Ludo; van den Berg, Leonard H.
Abstract: Introduction: We present a case series of six treatment‐naive patients with clinical phenotypes compatible with chronic inflammatory demyelinating polyneuropathy and multifocal motor neuropathy without electrodiagnostic features of demyelination but with abnormal peripheral ultrasound findings who responded to treatment. Methods: All six patients underwent a complete set of ancillary investigations, including extensive nerve conduction studies. We also performed standardized nerve ultrasound of median nerves and brachial plexus as part of a larger effort to evaluate diagnostic value of sonography. Results: Nerve conduction studies did not show conduction block or other signs of demyelination in any of the six patients. Sonographic nerve enlargement was present in all patients and was most prominent in proximal segments of the median nerve and brachial plexus. Treatment with intravenous immunoglobulin resulted in objective clinical improvement. Discussion: Our study provides evidence that nerve ultrasound represents a useful complementary diagnostic tool for the identification of treatment‐responsive inflammatory neuropathies.